Fragmented QRS Complex Predicts In‐Hospital Adverse Events and Long‐Term Mortality in Patients with Acute Pulmonary Embolism. Issue 5 (24th December 2015) - Cetin, Mehmet Serkan; Ozcan Cetin, Elif Hande; Arisoy, Fazil; Kuyumcu, Mevlüt Serdar; Topaloglu, Serkan; Aras, Dursun; Temizhan, Ahmet
Abstract : Background: Electrocardiographic (ECG) abnormalities in pulmonary embolism (PE) are increasingly reported, and mounting data have recommended that ECG plays a crucial role in the prognostic assessment of PE patient population. However, there is scarce data on the prognostic importance of fragmented QRS (fQRS) on short‐ and long‐term outcomes in patients with PE. Therefore, we aimed to investigate the prognostic role of fQRS in predicting in‐hospital and long‐term adverse outcomes in PE patients. Methods: A total of 249 patients (155 female, 66.2%; mean age, 66.0 ± 16.0) with the diagnosis of acute PE were enrolled and followed‐up during median 24.8 months. Results: Compared with the fQRS (−) patient group, patients with fQRS showed higher rates of in‐hospital adverse events including cardiogenic shock, the necessity of thrombolytic therapy, and in‐hospital mortality as well as long‐term all‐cause mortality. In Kaplan–Meier survival analysis, during follow‐up, all‐cause mortality occurred more frequently in the fQRS (+) group (log‐rank, P = 0.002). In multivariate Cox regression analysis, adjusted with other relevant parameters, the presence of fQRS were determined as an independent predictor of in‐hospital adverse events (HR: 2.743, 95% CI: 1.267–5.937, P = 0.003) and long‐term all‐cause mortality (HR: 3.137, 95% CI: 1.824–6.840, P = 0.001). Conclusions: The presence of fQRS complex, as a simple and feasible ECG marker, seems to be a novel predictor of in‐hospital adverse events and long‐term all‐cause mortality in PE patient population. This parameter may utilize the identification of patients whom at higher risk for mortality and individualization of therapy.